Factors Influencing Media Literacy Skills in the 21st Century among Nursing Students HRH Princess Chulabhorn College of Medical Science, Chulabhorn Royal Academy - Chailarp, Kanokwan; Lagampan, Sunee; Suwonnaroop, Nuntawun (Journal of The Royal Thai Army Nurses, 2022)
Media literacy is an essential skill in the 21st century. This skill enhances people to adapt and live happily in a disruptive world. This research aimed to study media literacy skill in the 21st century and its predictive factors among nursing students. The participants comprised 160 nursing students of faculty of nursing, HRH Princess Chulabhorn College of Medical Science, Chulabhorn Royal Academy. Data were collected through online questionnaires with 70 items. Using Descriptive statistics, Pearson’s correlation coefficient and stepwise multiple regressions were employed for data analysis. The results revealed that media literacy skills in the 21st century on practice showed the highest scores (mean = 102.9, SD = 11.05) and the skill on situation were relatively good (mean = 20.09, SD = 3.11). There were 4 influencing factors on the media literacy skills in the 21st century including Performance Expectancy (β = .26) Facilitating Conditions (β = .22), Social Influence (β = .24), and Habituation (β = .19) (p<.05). Stepwise multiple regression analysis revealed that those aforementioned factors could explain 34.2% of variance in media literacy skills in the 21st century on practice (F = 20.139; p-value <.05). This research recommended that teaching and learning management model should encourage students to develop their skills in using information media and technology both in theory and practice by determination of learning outcomes in terms of knowledge, attitudes, and information media skills that increase the level of intensity in each school year.